Katie Sutton. Sex between Body and Mind: Psychoanalysis and Sexology in the German-speaking World, 1890s-1930s. U of Michigan P, 2019. - Elizabeth Bridges (Studies in 20th & 21st Century Literature, 2021)
Review of Katie Sutton. Sex between Body and Mind: Psychoanalysis and Sexology in the German-speaking World, 1890s-1930s. U of Michigan P, 2019. 347 pp.
Keywords: book review; sexology; psychoanalysis; Hirschfeld; Freud; fin de siecle